The 3D Printability and Mechanical Properties of Polyhydroxybutyrate (PHB) as Additives in Urethane Dimethacrylate (UDMA) Blends Polymer for Medical Application - Ahmad Adnan Abu Bakar; Muhammad Zulhilmi Zainuddin; Shahino Mah Abdullah; Nizam Tamchek; Ikhwan Syafiq Mohd Noor; Muhammad Syafiq Alauddin; Ahmad Alforidi; Mohd Ifwat Mohd Ghazali (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA